Between Gaia and Ground : Four Axioms of Existence and the Ancestral Catastrophe of Late Liberalism - Povinelli, Elizabeth A. (Book collections on Project MUSE., 2021)
"Between Gaia and Ground examines four axioms of existence that have emerged in recent years across a significant segment of critical theory: the entanglement of existence; the unequal distribution of power to affect the local and transversal terrains of this entanglement; the multiplicity and collapse of the event as the sine qua non of political thought; and the racial and colonial history that informed modern western ontologies and epistemologies and the concept of the west as such. Beyond these axioms, Between Gaia and Ground is interested in the broader anticolonial struggles from which they emerged and a reactionary formation, late liberalism, which has attempted to remold, blunt, and redirect these struggles in the context of contemporary climatic, environmental, viral and social collapse. Elizabeth Povinelli treats these axioms as distinct theoretical statements, demonstrating that they are part of much broader discursive surfaces reflecting opposing currents in the direction of political thought and action in the wake of geontopower. Between Gaia and Ground seeks to show how a seemingly casual syntactic arrangement of theoretical statements results in dramatically differing paradigms for figuring the present as a coming catastrophe (l'catastrophe à venir) and as an ancestral one (l'catastrophe ancestral/histoire)"--